Clinical efficacy of the symbiotic drug Lotardi-A in the complex therapy of patients with irritable bowel syndrome in metabolic-associated fatty liver disease - Sirchak, Yelyzaveta (ScienceRise: Medical Science, 2025)
Irritable bowel syndrome (IBS) and metabolite-associated fatty liver disease (MAFLD) are among the most common gastrointestinal and liver diseases encountered in primary and secondary care. The aim of the study was to determine the clinical efficacy of treatment with the symbiotic drug Lotardi-A in the complex therapy of patients with IBS with MAFLD. Materials and methods. The study included 60 patients with IBS with MAFLD. Patients with IBS in combination with MAFLD were divided into two groups, depending on the method of treatment. The first group of patients (group I - n= 30) received only basic therapy aimed at correcting the functional state of the intestine and liver. The second group of patients (group II - n= 30), in addition to the basic treatment, received the symbiotic drug Lothardi-A. Results of the study. Additional administration of the symbiotic Lotardi-A to the subjects contributed to positive changes in the quantitative and qualitative composition of the colon microflora. A significant increase in the number of Bifidobacterium, Lactobacillus was determined. Evaluation of the dynamics of biochemical blood parameters after treatment, indicating the functional state of the liver in patients with IBS with MAFLD confirms more pronounced positive changes in laboratory parameters of cholestatic syndrome in the second group of patients. A significant decrease in the signs of cytolytic syndrome was also found. Conclusions: In patients with IBS and MAFLD, it is clinically more often manifested by constipation, namely in 43.3-46.7 %, respectively. These changes occur against the background of colon dysbiosis, mainly of the II and I stages (in 50.0 % and 36.7-40.0 % of the subjects). The treatment of patients with IBS and MAFLD should be comprehensive and include probiotic drugs. Prescription of Lothardi-A is an effective method for the correction of clinical manifestations of IBS, and is also a necessary component for the treatment of MAFLD and correction of dysbiotic changes. At the same time, in patients of group I with MAFLD and IBS with constipation, an increase in the frequency of defecation by 30.0 % (p<0.01) was found, while in patients of group I - only by 10.0 % (p<0.05). In 26.7 % of patients in group II after complex treatment, dysbiosis was not detected during repeated examination, while in group I, we did not find such patients. The additional administration of a symbiotic complex to patients with IBS in MAFLD is an effective means of complex treatment to reduce the severity of disorders of the functional state of the liver and lipid metabolism. At the same time, in patients of group II, a more pronounced significant decrease in serum ALT activity was found (decrease by 43.63±0.37 U/l - p<0.01). The same trend was found when assessing the level of triglycerides in the blood serum (decrease by 1.65±0.03 mmol/l - p<0.01)